Social desirability bias in PSM surveys and behavioral experiments: Considerations for design development and data collection. Issue 1 (January 2022) - Ried, Leopold; Eckerd, Stephanie; Kaufmann, Lutz
Abstract: Social desirability issues are long known, but not long gone. Across major purchasing and supply management (PSM) research streams, surprisingly few empirical studies explicitly address social desirability bias (SDB), despite SDB constituting a potentially limiting factor. With regard to surveys and behavioral experiments as two of the most widely used empirical methods in PSM, SDB can represent a critical issue. A first step should therefore be to collect and fully report data on SDB in all such studies. The present note then continues by providing an overview of methodological considerations for PSM researchers to mitigate social desirability issues before they arise in their surveys and behavioral experiments. We describe eight potential mitigation approaches, namely disguising the study's research purpose, assuring anonymity and confidentiality, indirect questioning, adapting the wording of single items, broadening response modes, conducting preparatory cognitive interviews, using multiple sources, and applying multiple research methods. In describing this repertoire of preventive measures, we point authors and review teams to both the broader methodological literature and PSM studies that have used such approaches. Highlights: A host of concepts and constructs across major PSM research streams are prone to Social Desirability Bias (SDB). A call is issued to make PSM research using experiments and surveys more transparent regarding and resilient against SDB. Eight concrete preventive measures are outlined that researchers can take to reduce SDB-related risks.